Teachers Perception on the Management of Inclusive Education in Elemantary School - Widodo, Agus Pratomo Andi; Hufad, Achmad; Sunardi, Sunardi (Journal of ICSAR, 2019)
The problem in this study was motivated by the difficulty of the teacher in implementing the Inclusive Education, which have been held since 2017 at the Sungai Andai 3 Elementary School in Banjarmasin. This study aims to describe the teacher’s perception of the implementation of Inclusive Education in Sungai Andai 3 Elementary School Banjarmasin, which covers 3 aspects according to the research questions, including: Teacher perceptions of the basic concept of  children with special needs, teacher perceptions of the education for children with special needs, and teacher perceptions of facilities and infrastructure. This study uses a type of qualitative research with a descriptive approach. Information about the perceptions of each respondent was revealed through questionnaires with 22 statements and in-depth interviews as data collection techniques and documentation. Data analysis techniques in this study are data reduction, data presentation, and conclusion. The teacher referred to in this study is a class teacher and subject teacher, as well as GPK or shadow teacher without any background of special education. This study was conducted on 23 respondents who teach at Sungai Andai 3 Elementary School in Banjarmasin . The results of the study are related to the purpose of the study that the teacher’s perception of the basic concept of children with special needs was “Good”. While the Teacher’s Perception of children with special need’s education and infrastructure facilities was “Enough”. Therefore, it is concluded that the teacher’s perception of the implementation of inclusive education in Sungai Andai 3 SDN Banjarmasin was “Good”.